Pengembangan Kualitas Konten Informasi Display Masjid Berbasis Web - Mohammad Sholik; Achmad Muzakki; Ardian Yusuf Wicaksono (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2023)
Digital transformation is a necessity that must be faced by various fields, including the religious field. The mosque, as a place of worship that has religious activities, needs to provide quality information to the community around the mosque, especially the congregation praying five times a day at the mosque. The Nurul Huda Mosque is located in Lowayu Village, Dukun Sub-district, Gresik Regency. Until now, information on religious activities has only been conveyed through loudspeakers, so the information conveyed is limited to certain times, which is likely to have many congregations and the community around the mosque who do not know about it. It is necessary to improve the quality of information through web-based information management training using computer media for religious activities, which are transmitted digitally through digital screens available in the foyer of the mosque. The results of the assistance provided an increase in perception and knowledge for the management of the mosque's digital information management section with a score of 4.33 (very appropriate), and the level of partner satisfaction with the community service program as a whole got an average score of 4.06 (satisfied).